Assessing extreme enantiomeric purity of (+)-1-(9-Fluorenyl)ethyl chloroformate by normal- and reversed-phase enantioselective chromatography: toward greener analytical strategies - Simone Manetto; Giulia Mazzoccanti; Elena Tuzi; Fabrizio Giorgi; Cristina di Giovanni; Michela Forte; Alessia Ciogli; Francesco Gasparrini (Analytica Chimica Acta, 2026)

National-scale analysis of extinction risk correlates in Italian flowering plants - Angelino Carta; Margherita Gioria; Elena Zappa; Mariacristina Villani; Simonetta Bagella; Sara Magrini; Annalisa Santangelo; Emmanuele Farris; Giulia Calderisi; Donatella Cogoni; Maria Silvia Pinna; Gianpietro Giusso del Galdo; et al. (Biological Conservation, 2026)

Tracing plant invasions in freshwater habitats: spatial and temporal insights from herbarium metadata - Emanuele Pelella; Diego Cantini; Simona Ceschin; Lorenzo Pinzani; Dario Di Lernia; Sebastiano Andreatta; Simonetta Bagella; Giovanna Barbieri; Elena Barni; Fabrizio Bartolucci; Eugen Behrens; Rossano Bolpagni; et al. (Hydrobiologia, 2026)

Combined sewer overflow contribution to microplastic pollution in urban water bodies - Elena Vannini; Simona Francalanci; Simone Lippi; Stefano Tempestini (Science of The Total Environment, 2026)

Hydrogeological and vegetational assessment of Fontanili (lowland springs) in Southern Turin Po Plain (Italy): conservation and environmental impacts - Federico Emanuel Franco; Sara Giammario; Marica Tumminello; Maria Rita Minciardi; Concita Daniela Spada; Simone Ciadamidaro; Domenico Antonio De Luca; Elena Egidio; Daniele Cocca; Manuela Lasagna (Sustainable Water Resources Management, 2026)
This study presents the hydrogeological and vegetational context of lowland springs -known in Italian as risorgive or fontanili - in a sector of the southern Po Plain near Turin (north-western Italy). Despite their important ecological role, these springs remain understudied, particularly regarding the effects of climate change and human activities. Not included in Italy’s environmental protection regulations and often poorly maintained, they require accurate identification and characterisation to support monitoring and management by local authorities. This study adopts a multidisciplinary approach, combining hydrogeological analysis with vegetation surveys, an integration rarely found in recent literature. Fontanili in the study area were mapped, and two field campaigns were conducted in summer and autumn 2022. A total of 92 springs was identified, of which only 26 were active during the study period due to prolonged drought. Hydrochemical and piezometric analyses of the shallow aquifer were performed, alongside vegetation surveys carried out at 28 springs in autumn 2022 and spring 2023. Hydrochemical data revealed a contrast between groundwater and surface water characteristics, with calcium bicarbonate prevailing in groundwater and calcium sulphate in surface water. Vegetation data indicated a loss of hygrophilous species linked to water scarcity, along with an increase in invasive alien species. The results highlight the vulnerability of these ecosystems and the urgent need for their conservation. The study aims to raise awareness, promote further research, and encourage local authorities to take concrete action for the protection of these unique lowland spring habitats.

Forest structure and multi-taxonomic diversity in Apennine beech forests subjected to conservation-oriented interventions - Mirko Legnaro Diamanti; Giacomo Cangelmi; Luciano Ludovico Maria De Benedictis; Lorenzo Balducci; Renato Benesperi; Elisabetta Bianchi; Emanuela Carli; Andrea Ceci; Francesco Chianucci; Giampiero Ciaschetti; Leopoldo De Simone; Andrea De Toma; et al. (Plant Biosystems, 2026)

Tracing herding strategies in the Samarkand Oasis: isotopic and proteomic insights from Kafir Kala (Samarkand, Uzbekistan) - Elena Armaroli; Federico Lugli; Eleonora Serrone; Beatrice Demarchi; Marlisa Mazzola; Sarah Sandron; Samaretdin Suyunov; Amriddin Berdimuradov; Hubert Vonhof; Simone Mantellini; Anna Cipriani (Archaeological and Anthropological Sciences, 2026)
The archaeological complex of Kafir Kala is one of the most important sites in the Samarkand oasis, strategically located just a few miles from the main city and along the major junction of the Silk Road. After more than twenty years of systematic archaeological investigation, the importance of Kafir Kala as a nodal point within the broader Eurasian connection network was recognised by its inclusion on the UNESCO World Heritage List in 2023 as part of the Silk Roads. During both the Pre-Islamic (second half of the 7th – early 8th century AD) and the Islamic (early 8th – 12th century AD) phases, ovicaprids were the predominant species in the faunal record. To date, stable isotope analysis from Uzbek archaeological sites is very limited, with no data available for fauna. Similarly, despite the region’s historical role in mobility and exchange, 87 Sr/ 86 Sr analysis has been applied in only a few archaeological contexts. Here, we present the results of a multi-proxy study including proteomic (Zooarchaeology by Mass Spectrometry - ZooMS) and isotope ( 87 Sr/ 86 Sr, δ 13 C, δ 18 O) analyses on twenty ovicaprid teeth from the Islamic phase of Kafir Kala to gain insights into the management strategies of the most represented species in the local faunal record. The identification of at least two different breeding strategies – marked by clear differences between sheep and goats – together with evidence of contacts with foreign groups, is consistent with enduring local traditions and further highlights the dynamic role of Kafir Kala at the crossroads of the ancient Silk Road trade networks.

Corrigendum to “Comparative genomics of Cladosporium reveals limited evidence of selective pressure in soils historically contaminated with hexachlorocyclohexane and polychlorinated biphenyls” [J. Environ. Chem. Eng. 14(2)] - Giampiero De Simone; Elena Andreotti; Nicola Bertelloni; Laurence Fraissinet-Tachet; Thibault Le Gratiet; David Chapulliot; Janice Bamforth; Sean Walkowiak; Giulio Petroni; David Levin; Simona Di Gregorio (Journal of Environmental Chemical Engineering, 2026)

Effect-based methods and effect-based trigger values for estrogenicity monitoring in surface water: an interlaboratory study - Livia Gómez; Dimitar Marinov; Elena Porcel-Rodríguez; Diletta Scaccabarozzi; Isabella Sanseverino; Pietro Sciuto; Frank Narendja; Romana Hornek-Gausterer; Katharina Lenz; Carole Chalon; Yves Marneffe; Přemysl Soldán; et al. (Environmental Research, 2026)

A dataset of plant communities invaded by Acacia sp. pl. and Robinia pseudoacacia in Italy - Eugenia Siccardi; Alice Misuri; Alicia Teresa Rosario Acosta; Claudia Angiolini; Dario Azzaro; Gianluigi Bacchetta; Simonetta Bagella; Elena Barni; Giuseppe Bazan; Maria E. Boi; Gianmaria Bonari; Giuseppe Brundu; et al. (Plant Biosystems, 2026)
The full extent of the ecological threat posed by non-native invasive leguminous N-fixing trees to Italian ecosystems has not been thoroughly documented at the national level. This study, conducted by the Working Group on Alien Species of the Italian Botanical Society, aims to develop a comprehensive dataset that provides information on invaded and non-invaded areas, supporting multi-scale ecological analyses on the impact of black locust ( Robinia pseudoacacia ) and different Acacia sensu lato species across Italy. We conducted paired vegetation surveys across 18 distinct invasion contexts, comparing invaded and non-invaded plant communities. These invasion contexts were selected opportunistically by the participating research groups, based on the availability of well-documented sites where the focal species were already established and exerting ecologically relevant effects. Overall, we conducted 342 vegetation surveys across 10 Italian administrative regions and identified 824 plant species. Our surveys highlighted areas affected by five invasive species, including A. dealbata, A. mearnsii, A. saligna , Vachellia karroo , and R. pseudoacacia . Most of the surveys focused on areas invaded by A. saligna . The plant formations investigated fall under 23 EUNIS habitat codes and 10 Natura 2000 habitats. The most frequently occurring vegetation types under the EUNIS code are temperate and Mediterranean-montane scrub, and the most frequently investigated habitat is priority habitat 2250*: Coastal dunes with Juniperus sp. pl. This dataset provides a robust baseline that can facilitate more detailed assessments of the impacts of these invasive species on native ecosystems.

Higher plasma serine levels are associated with favorable values of metabolic health markers among middle-aged and older adults in The Maastricht Study - Thomas Olsen; Amany Elshorbagy; Elena C. Tore; Nasser E. Bastani; Emma Stolt; Gabriëlla A. M. Blokland; Coen D. A. Stehouwer; M. Eline Kooi; Jacobus F. A. Jansen; Simone J. P. M. Eussen; Pol Grootswagers; Helga Refsum; et al. (GeroScience, 2026)

Comparative genomics of Cladosporium reveals limited evidence of selective pressure in soils historically contaminated with hexachlorocyclohexane and polychlorinated biphenyls - Giampiero De Simone; Elena Andreotti; Nicola Bertelloni; Laurence Fraissinet-Tachet; Thibault Le Gratiet; David Chapulliot; Janice Bamforth; Sean Walkowiak; Giulio Petroni; David Levin; Simona Di Gregorio (Journal of Environmental Chemical Engineering, 2026)

Direct Analysis of Per- and Polyfluoroalkyl Substances (PFAS) in Plasma by Liquid Chromatography Coupled to Mass Spectrometry (LC–MS) for Biomonitoring Purposes - Arianna Fornasari; Paolo Fais; Annamaria De Luca; Giovanni Dal Lago; Simone Santelli; Guido Pelletti; Elena Piva; Jennifer Pascali (Exposure and Health, 2026)
A rapid and direct liquid chromatography–mass spectrometry (LC–MS) method was developed and validated for high-throughput biomonitoring of Per- and Polyfluoroalkyl Substances (PFAS) in human plasma. This approach streamlines the analytical workflow by replacing traditional, labor-intensive solid-phase extraction (SPE) with a simple protein-precipitation step. Twenty-three PFAS (PFBA, PFPeA, PFHxA, PFHpA, PFOA, PFNA, PFDA, PFUnA, PFDoA, HFPO-Da, PFMPA, PFMBA, PFBS, PFPeS, PFHpS, PFOS, ADONA, 4:2 FTS, 6:2 FTS, 8:2 FTS, 9Cl-PF3ONS, 11Cl-PF3OUdS, PFEESA) were monitored. Method detection limits (MDLs) and limits of quantification (LOQs) ranged from 0.01 to 0.39 ng/mL and from 0.04 to 1.2 ng/mL, respectively. Accuracy (bias) and precision (RSD) were below 16% and 10%, respectively, for all PFAS in both intra- and inter-day experiments. Recoveries ranged from 86 to 102%, and matrix effects were estimated as ion suppression below 30% for all analytes. The method was successfully applied to a cohort of 426 Italian citizens who participated on a voluntary basis. Twelve PFAS were detected, with PFOS and PFOA present in 95% of the samples. The mean and median sums of detected PFAS were 7.3 ng/mL (SD 4.6) and 6.2 ng/mL $$IQR4.4{-}9.2$$ , respectively, with a maximum total concentration of 35 ng/mL. PFOS isomers (linear + branched) contributed the most to the total PFAS burden in plasma, reaching a maximum concentration of 25 ng/mL. Overall, this method proved to be a reliable and efficient tool for large-scale biomonitoring studies and provides an important basis for investigating the long-term health implications of PFAS exposure.

The Italian effort toward a coordinated observation of Essential Variables (EOV, ECV, EBV) in European Marine Environments. Long-term observation in the central Mediterranean seas and Italian coasts - Simone Toller; Emilio Urbinati; Debora Bellafiore; Caterina Bergami; Francesca De Pascalis; Marcello G. Magaldi; Marco Bellacicco; Federico Bellati; Maristella Berta; Angelo Boccacci; Roberto Bozzano; Fabio Brunetti; et al. (Frontiers in Marine Science, 2026)
Monitoring Essential Ocean, Climate, and Biodiversity Variables (EOVs, ECVs and EBVs) collected through the marine Research Infrastructures (RIs) is critical for assessing environmental status, improving scientific knowledge and defining environmental policies. This study evaluates the capacity of the Italian marine monitoring system, including facilities such as fixed stations, buoys, autonomous platforms, and mobile systems across the Mediterranean Sea, to produce those variables. Conducted in 2023 within the framework of the ITINERIS project ( https://itineris.cnr.it/ ), which aims to strengthen coordination among national and ESFRI RIs (European Strategy Forum on Research Infrastructures), the analysis systematically examines the spatial, thematic, and technological coverage of EOVs, ECVs, EBVs observations and their alignment with international standards for environmental monitoring of 155 facilities from eight Italian and pan-European marine RIs. Of the 107 EVs recognized, 50% were actively produced by the RIs considered, with over 90% meeting the established requirements for EVs. These numbers will be updated to reflect the new equipment acquired during the project’s implementation up to early 2026, which is expected to boost EVs production by approximately 38-40%. The national monitoring network demonstrates a high degree of maturity for oceanic and climate variables, while biodiversity observations remain less represented, indicating the need for further technological innovation and automation. These findings emphasize the importance of enhancing coordination and harmonization among RIs to ensure balanced and interoperable monitoring. The study provides key recommendations to strengthen Italy’s capacity to contribute to the global characterization of EOVs, ECVs, and EBVs and to support evidence-based environmental assessments and the development of robust environmental management strategies at European level.

Tribology of dual Pickering double emulsions: Machine learning-aided inner droplet analysis - Elizabeth Tenorio-Garcia; Siavash Soltanahmadi; Jens Saalbrink; Jose C. Bonilla; Michael Rappolt; Elena Simone; Anwesha Sarkar (Food Hydrocolloids, 2026)

Designing for reuse in timber buildings: The environmental benefits of aligning the time of nature and time of use - Nicoletta Patrizi; Fabio Sporchia; Anna Ruini; Elena Neri; Morena Bruno; Giulia Zarroli; Simone Bastianoni; Nadia Marchettini (Resources, Conservation and Recycling, 2026)

Easy at home, difficult at the restaurant: Perceived effectiveness and feasibility of self-control strategies for reducing meat consumption - Alice Elena Seffen; Rebecca Blase; Simone Dohle (Food Quality and Preference, 2026)

Debunking meat myths using the truth sandwich: A longitudinal experiment among German meat consumers - Alice Elena Seffen; Nina Weingarten; Charlotte Mai; Simone Dohle (Food Quality and Preference, 2026)

P and S wave finite-frequency tomography reveals the impact of slab interference on mantle flow beneath the greater Alpine region - Yuantong Mao; Xiaotian Tang; Liang Zhao; Marco G. Malusà; Stéphane Guillot; Anne Paul; Stefano Solarino; Xiaobing Xu; Coralie Aubert; Elena Eva; Silvia Pondrelli; Simone Salimbeni; et al. (Earth and Planetary Science Letters, 2026)

Tristearin and C12–18 saturated fatty acids blends: Interplay between eutectic phase behaviour and polymorphic transition - Serena Bertoni; Elena Simone; Beatrice Albertini; Nadia Passerini (Food Research International, 2025)

Synthetic debris ingestion by carnivorous mammals in aquatic ecosystems: insights from the Eurasian otter (Lutra lutra) in Europe - Álvaro Luna; David León Muez; Ignacio G. Hermosell; Elena Ávila Falcón; Simone Giovacchini; Enrico Mirone; Miguel Ángel Gómez-Serrano; Ángel Fernández González; Hugh Jasman; Arjen de Groot; Václav Beran; Lukáš Poledník; et al. (Environmental Research, 2025)

Heyndrickxia coagulans LMG S-24828 Is a Safe Probiotic Strain Capable of Germinating in the Human Gut - Robin Duncan; Giacomo Mantegazza; Giorgio Gargari; Elena Pierallini; Rosario Russo; Simone Guglielmetti (Probiotics and Antimicrobial Proteins, 2025)

Prenatal exposure to fine particulate matter PM2.5 and small for gestational age: a Bayesian model for area-based data in Milan - Simone Colombara; Rossella Murtas; Sara Tunesi; Alessandra Guglielmi; Antonio Giampiero Russo; Paola Angelini; Serena Broccoli; Marco Monti; Nicola Caranci; Katia Raffaelli; Daniela Fortuna; Paolo Giorgi Rossi; et al. (Environmental and Ecological Statistics, 2025)

Impact of light intensity on purple phototrophic bacteria mixed cultures: experimental insights and biokinetic modelling - Ali Amini; Simone Rossi; Valiallah Amirian Mojarad; Gabriele Bellotti; Fabrizio Cappa; Filippo Vaccari; Edoardo Puglisi; Roberto Canziani; Elena Ficara; Andrea Turolla (Bioresource Technology, 2025)

Monsoon variability and high latitude climate signals in the Central Mediterranean at the Pliocene- Pleistocene transition: The Gelasian stratotype section (Monte San Nicola, Sicily) [Global and Planetary Change, volume 249, 104788]: Comment - Elena Zanola; Sergio Bonomo; Alessandro Incarbona; Telemaco Tesei; Agata Di Stefano; Patrizia Ferretti; Eliana Fornaciari; Simone Galeotti; Patrizia Macrì; Isabella Raffi; Teresa Rodrigues; Fabio Speranza; et al. (Global and Planetary Change, 2025)

Integrating ethical assessment and media content analysis to explore social conflicts over large carnivores - Simone Basile; Elena Mercugliano; Sally Carraro; Pierfrancesco Biasetti; Giulia Mascarello; Anna Pinto; Marco Zago; Veronica Nanni; Steven Seet; Roberto Guadagnini; Barbara de Mori (Biological Conservation, 2025)

Using Local Ecological Knowledge (LEK) to inform the multi-habitat life cycle of wreckfish: A Ligurian Sea case study for Mediterranean conservation - ELENA DESIDERÀ; DAVIDE DI BLASI; FEDERICA POLI; TREVOR J. WILLIS; SIMONE BAVA; PAOLO GUIDETTI (Mediterranean Marine Science, 2025)
Local Ecological Knowledge (LEK) from fishers and sea users is invaluable for reconstructing the occurrences of data deficient and vulnerable fish species, particularly target species. This study explores the distribution patterns of the data-deficient wreckfish Polyprion americanus in the Ligurian Sea (NW Mediterranean Sea) using semi-structured interviews with 40 sea users (27 fishers and 13 observational data providers). We identified key habitats associated with five main size classes of wreckfish, from surface waters to 1000 m depth, including vulnerable ecosystems like seamounts and cold-water coral habitats. Smaller individuals (0-1.5 kg) were mainly found in pelagic habitats, frequently near floating objects, while larger individuals (>3 kg) were common in slope and seamount habitats. Abundance declines across all size classes were attributed to overfishing and, according to some respondents, a reduction in floating debris may have specifically affected the presence of smaller individuals. Fishing techniques varied by size class, with technological advances notably impacting larger individuals near seamounts. The study supports LEK as a valuable complementary information source to conventional research, advocating for updated conservation measures, including revised size limits and enhanced protection of vulnerable habitats.

Chiral resolution of 3-monochloro-1,2-propanediol optical isomers in edible oils: From ester hydrolysis to enantiomeric analysis - Alessia Lanno; Michela Torrelli; Simone Stefano; Alice Passoni; Sofia Ghironi; Renzo Bagnati; Elena Fattore; Enrico Davoli (Food Chemistry, 2025)

Geochemical fingerprinting of extra virgin olive oils based on radiogenic strontium isotopes - Samuel Pelacani; Simone Tommasini; Mattia Ferrari; Matthias Ghiotto; Elena Pecchioni; Roberto Riccio; Sandro Moretti (Science of The Total Environment, 2025)

Investigating the effect of animal visualisations on meat choice: An experimental lab study with a fake food buffet - Nina Weingarten; Alice Elena Seffen; Leonie Bach; Julia Meis-Harris; Anna Aeikens; Sara Barbieri; Simone Dohle (Food Quality and Preference, 2025)

Chemical emissions from offshore wind farms: From identification to challenges in impact assessment and regulation - Elena Hengstmann; Pablo Zapata Corella; Katharina Alter; Maria J. Belzunce-Segarra; Andy M. Booth; Javier Castro-Jiménez; Niklas Czerner; Karien De Cauwer; Geneviève Deviller; Alessio Gomiero; Nils Goseberg; Simone Hasenbein; et al. (Marine Pollution Bulletin, 2025)

Assessing the activity and stability of Cu2O/SnO2-based gas diffusion electrodes for the CO2 conversion in different electrolytes: Bicarbonate vs. Ionic Liquid/Acetonitrile - Federica Zammillo; Hilmar Guzmán; Daniela Polino; Roger Miró; Alberto Lopera; Emmanuele Parisi; Alessia Fortunati; Maddalena Zoli; Elena Simone; Nunzio Russo; Mariajose López-Tendero; Miriam Díaz de los Bernardos; et al. (Chemical Engineering Journal, 2025)

Finding relevant stakeholders and related social topics for the implementation of Social Life Cycle Assessment in the multistorey timber construction sector - Morena Bruno; Laura Zanchi; Nicoletta Patrizi; Elena Neri; Madalina Rusen; Pietro Elisei; Carmela Gioia; Federico Maria Pulselli; Simone Bastianoni (The International Journal of Life Cycle Assessment, 2025)
Purpose This study aims to identify the most relevant stakeholder groups and related social topics for the multistorey timber construction sector and provide first insights on the potential social effects—negative (risks) and positive (benefits)—produced by the prospective increase of multistorey timber constructions in Europe considering their whole life cycle. Methods The advancement of social materiality assessment was conducted to unveil the most relevant stakeholder groups and related social topics of the building sector by considering what is proposed by the UNEP Guidelines for Social Life Cycle Assessment and Handbook for Product Social Impact Assessment. To verify selected social topics and collect information on their level of relevance, we based our research approach on stakeholder engagement through a dedicated online workshop and interviews. Results Seventeen social topics were selected as material for the multistorey timber construction sector according to the literature review and the stakeholder engagement activities. No significant variance in relevance level was observed according to a five-level Likert scale (from 1, not at all relevant, to 5, very relevant), all rating above level 3 (relevant); the ones perceived as very relevant being “Health and safety” (Users), “Safe and healthy living conditions” (Local Community), and “Fair salary” (Workers). Conclusions This study highlights how conducting a social materiality assessment and engaging stakeholders play a crucial role in identifying an initial set of critical social topics to focus on for further evaluation of potential impacts and performance. Since there is not yet a standardized approach for the S-LCA application in the construction sector, results from this work represent an initial step towards the prioritization process of social topics. This prioritization process aims to assign priority levels to a list of social topics derived from a review process based on various sources.

Plant subsistence and environment in the Late Bronze Age of the Central Black Sea Region: archaeobotanical remains from Oymaağaç Höyük/Nerik and their Anatolian context - Corinna Rössner; Ivanka Hristova; Simone Riehl; Elena Marinova (Archaeological and Anthropological Sciences, 2025)
This archaeobotanical study represents the first comprehensive study of the Late Bronze Age Hittite subsistence use of plants and woodland vegetation in the Black Sea region. Seed/fruit and wood-charcoal analyses were conducted to gain insight into the plant-based economy of the site. The economic seed plants reveal that the main annual crops were barley, free-threshing wheat, and emmer, along with pulses like lentil, bitter vetch, grass pea, broad bean, and garden pea. In addition, a variety of fruits and nuts were used. The charcoal analyses show the use of different woodland types and, together with the spectrum of wild plant macrofossils, paint a picture of extensive anthropogenic activity on the natural vegetation. Previous research postulated that Hittite agriculture was strongly influenced by cultural and political factors. The climatic conditions and the natural environment of the Hittite sites played a less important role in the choice of agricultural products than traditional ties to systematic surplus production of specific crops. To test this hypothesis, we compare seed assemblages from Oymaağaç Höyük with those from other Late Bronze Age and Hittite settlements in Anatolia and northern Syria and investigate possible environmental constraints and cultural trends. Climatic factors, such as the general regional climate patterns as well as mean annual precipitation, were taken into consideration when discussing the plant diversity. Our results confirm a strong cultural pattern of plant subsistence at Oymaağaç Höyük, which is similar to that in other Hittite sites in Central Anatolia, while it differs from other non-Hittite settlements with comparable rainfall regimes.

A peculiar coral formation in the Mediterranean Sea, and its associated biota - Roberto Arrigoni; Elena Desiderà; Simone Bava; Carla Morri; Carlo Nike Bianchi; Paolo Guidetti (Ecology, 2025)

Corrigendum to “Health risk assessment for dietary exposure to 3-monochloropropane-1,2-diol, 2-monochloropropane-1,3-diol, and glycidol for Italian consumers” [Chemosphere 365 (2024) 143339] - Alessia Lanno; Simone Stefano; Sofia Ghironi; Michela Torrelli; Alice Passoni; Renzo Bagnati; Alessandra Roncaglioni; Enrico Davoli; Elena Fattore (Chemosphere, 2025)

Bronchial foreign body caused by a grasshopper in a dog - Giulia Maggi; Elena Rosi; Simone Cupido; Salvatore Palma; Maria Chiara Marchesi (Veterinary Research Communications, 2025)
An 11-year-old dog living in a rural area of Italy was evaluated for a persistent cough. Diagnostic imaging findings, combined with the clinical history and physical examination, revealed focal pneumonia, raising suspicion of a vegetal foreign body. Bronchoscopy identified a foreign body (a grasshopper) partially obstructing the left caudal bronchus, and its removal was successfully performed. Insects should be considered potential bronchial foreign bodies in the differential diagnosis.

Complementing emergy evaluation and life cycle assessment for enlightening the environmental benefits of using engineered timber in the building sector - Fabio Sporchia; Morena Bruno; Elena Neri; Federico M. Pulselli; Nicoletta Patrizi; Simone Bastianoni (Science of The Total Environment, 2025)

Evidence of oxidative stress in the soft coral Pinnigorgia flava (Nutting, 1910) exposed to secondary plastic nanofibers and related leachates - Valerio Isa; Davide Seveso; Eleonora Concari; Alessandro Becchi; Francesco Saliu; Marina Lasagni; Elena Maria Collina; Andrea Madaschi; Silvia Lavorano; Simone Montano; Yohan Didier Louis; Enrico Montalbetti (Environmental Pollution, 2025)

Modeling the spatial distribution and abundance of deep‐water red shrimps in the Mediterranean Sea: a machine learning approach - Elena Catucci; Diego Panzeri; Simone Libralato; Gianpiero Cossarini; Germana Garofalo; Irida Maina; Stefanos Kavadas; Federico Quattrocchi; Giulia Cipriano; Roberto Carlucci; Sergio Vitale; Chryssi Mytilineou; et al. (Fisheries Research, 2025)

Seismic tomography reveals contrasting styles of subduction-channel and mantle-wedge exhumation controlled by upper plate divergent motion - Stefano Solarino; Marco G. Malusà; Elena Eva; Anne Paul; Stéphane Guillot; Silvia Pondrelli; Simone Salimbeni; Liang Zhao (Gondwana Research, 2024)

Ethical assessment of genome resource banking (GRB) in wildlife conservation - Pierfrancesco Biasetti; Elena Mercugliano; Lisa Schrade; Maria Michela Spiriti; Frank Göritz; Susanne Holtze; Steven Seet; Cesare Galli; Jan Stejskal; Silvia Colleoni; Daniel Čižmár; Raffaella Simone; et al. (Cryobiology, 2024)

Association between long-term exposure to air pollution and cause-specific mortality within five Italian longitudinal metropolitan studies - Federica Nobile; Nicola Caranci; Elena Strippoli; Valentina Adorno; Alessandra Allotta; Lucia Bisceglia; Ida Galise; Claudio Gariazzo; Sara Maio; Paola Michelozzi; Walter Pollina Addario; Andrea Ranzi; et al. (Atmospheric Environment, 2024)

High prevalence and genetic heterogeneity of adenoviruses at a psittacine breeding facility - Gabriele Lizzi; Simone Fasana; Guido Grilli; Giulia Quaglia; Sara Pedrazzoli; Giulia Graziosi; Elena Catelli; Laura Musa; Maria Cristina Rapi; Caterina Lupini (Veterinary Research Communications, 2024)
A polymerase chain reaction (PCR) survey was performed at an amateur parrot breeding facility in Italy to investigate the presence and molecular characteristics of adenoviruses. Eighty psittacine birds, belonging to seven parrot species, were sampled by cloacal swabs; in addition, 15 livers were collected from specimens that were found dead. Seventy-two out of 95 samples collected were positive for adenoviruses, with a prevalence rate of 75.8%. All seven psittacine species tested positive for at least one genus of the family Adenoviridae ; notably, adenoviral infection was found for the first time in the hooded parrot ( Psephotellus dissimilis ). Based on the sequences and phylogenetic analysis, 57 sequences were psittacine adenovirus 2, seven sequences were duck adenovirus 1 and two sequences were identified as psittacine adenovirus 5. The six remaining sequences showed low nucleotide and amino acid identity with the reference strains of accepted species or types, revealing the presence of novel adenoviruses belonging to the genera Aviadenovirus , Barthadenovirus and Siadenovirus . There were identical adenovirus sequences in both apparently healthy and dead birds suggesting that further investigation into the role and impact of these viruses on the health of psittacine birds is warranted.

Fabrication and stability of dual Pickering double emulsions stabilized with food-grade particles - Elizabeth Tenorio-Garcia; Michael Rappolt; Amin Sadeghpour; Elena Simone; Anwesha Sarkar (Food Hydrocolloids, 2024)

Health risk assessment for dietary exposure to 3-monochloropropane-1,2-diol, 2-monochloropropane-1,2-diol, and glycidol for Italian consumers - Alessia Lanno; Simone Stefano; Sofia Ghironi; Michela Torrelli; Alice Passoni; Renzo Bagnati; Alessandra Roncaglioni; Enrico Davoli; Elena Fattore (Chemosphere, 2024)

Gut-lung microbiota dynamics in mice exposed to Nanoplastics - Nur Kaluç; Sara Bertorello; Oğuz Kaan Tombul; Simone Baldi; Giulia Nannini; Gianluca Bartolucci; Elena Niccolai; Amedeo Amedei (NanoImpact, 2024)

A crystal engineering approach for rational design of curcumin crystals for Pickering stabilization of emulsions - Giulia Del Duca; Emmanuele Parisi; Fiora Artusio; Eleonora Calì; Silvia Fraterrigo Garofalo; Chiara Rosso; Valentina Cauda; Michele R. Chierotti; Elena Simone (Food Research International, 2024)

Comprehensive characterization of bacterial glycoconjugate vaccines by liquid chromatography - mass spectrometry - Fiammetta Di Marco; Agnes L. Hipgrave Ederveen; Guusje van Schaick; Alan B. Moran; Elena Domínguez-Vega; Simone Nicolardi; Constantin Blöchl; Carolien A. Koeleman; Renzo Danuser; Ali Al Kaabi; Viktoria Dotz; Jan Grijpstra; et al. (Carbohydrate Polymers, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

An early Transcriptomic Investigation in Adult Patients with Spinal Muscular Atrophy Under Treatment with Nusinersen - Maria Liguori; Annalisa Bianco; Alessandro Introna; Arianna Consiglio; Giammarco Milella; Elena Abbatangelo; Eustachio D’Errico; Flavio Licciulli; Giorgio Grillo; Isabella Laura Simone (Journal of Molecular Neuroscience, 2024)
Spinal muscular atrophy (SMA) is a rare degenerative disorder with loss of motor neurons caused by mutations in the SMN1 gene. Nusinersen, an antisense oligonucleotide, was approved for SMA treatment to compensate the deficit of the encoded protein SMN by modulating the pre–mRNA splicing of SMN2 , the centromeric homologous of SMN1 , thus inducing the production of a greater amount of biologically active protein. Here, we reported a 10-month transcriptomics investigation in 10 adult SMA who received nusinersen to search for early genetic markers for clinical monitoring. By comparing their profiles with age-matched healthy controls (HC), we also analyzed the changes in miRNA/mRNAs expression and miRNA-target gene interactions possibly associated with SMA. A multidisciplinary approach of HT-NGS followed by bioinformatics/biostatistics analysis was applied. Within the study interval, those SMA patients who showed some clinical improvements were characterized by having the SMN2/SMN1 ratio slightly increased over the time, while in the stable ones the ratio decreased, suggesting that the estimation of SMN2/SMN1 expression may be an early indicator of nusinersen efficacy . On the other hand, the expression of 38/147 genes/genetic regions DE at T0 between SMA and HC like TRADD and JUND resulted “restored” at T10. We also confirmed the dysregulation of miR-146a(-5p), miR-324-5p and miR-423-5p in SMA subjects. Of interest, miR-146a-5p targeted SMN1 , in line with experimental evidence showing the key role of astrocyte-produced miR-146a in SMA motor neuron loss. Molecular pathways such as NOTCH, NF-kappa B, and Toll-like receptor signalings seem to be involved in the SMA pathogenesis.

Geophysical evidence of large-scale silica-rich fluid flow above the continental subduction interface - Yuantong Mao; Liang Zhao; Marco G. Malusà; Stefano Solarino; Silvia Pondrelli; Baolu Sun; Coralie Aubert; Simone Salimbeni; Elena Eva; Stéphane Guillot (Science China Earth Sciences, 2024)

Best practices, errors, and perspectives of half a century of plant translocation in Italy - Martina D'Agostino; Luigi Cao Pinna; Marta Carboni; Silvia Assini; Gianluigi Bacchetta; Fabrizio Bartolucci; Lisa Brancaleoni; Fabrizio Buldrini; Angelino Carta; Bruno Cerabolini; Roberta Maria Ceriani; Umberto Clementi; et al. (Conservation Biology, 2024)
Conservation translocations are becoming common conservation practice, so there is an increasing need to understand the drivers of plant translocation performance through reviews of cases at global and regional levels. The establishment of the Italian Database of Plant Translocation (IDPlanT) provides the opportunity to review the techniques used in 186 plant translocation cases performed in the last 50 years in the heart of the Mediterranean Biodiversity Hotspot. We described techniques and information available in IDPlanT and used these data to identify drivers of translocation outcomes. We tested the effect of 15 variables on survival of translocated propagules as of the last monitoring date with binomial logistic mixed‐effect models. Eleven variables significantly affected survival of transplants: life form, site protection, material source, number of source populations, propagation methods, propagule life stage, planting methods, habitat suitability assessment, site preparation, aftercare, and costs. The integration of vegetation studies in the selection of suitable planting sites significantly increased the success of translocation efforts. Although posttranslocation watering had a generally positive effect on translocation outcome, other aftercare techniques did not always increase transplant survival. Finally, we found that how funds were spent appeared to be more important than the actual amount spent. Plant translocations in Italy and in the Mediterranean area should account for the complexity of speciation, gene flow, and plant migrations that has led to local adaptations and has important implications for the choice and constitution of source material.

Meta-analysis of the Cetacea gut microbiome: Diversity, co-evolution, and interaction with the anthropogenic pathobiome - Elena Radaelli; Giorgia Palladino; Enrico Nanetti; Daniel Scicchitano; Simone Rampelli; Sabina Airoldi; Marco Candela; Marianna Marangi (Science of The Total Environment, 2024)

Quantitative determination of tetracyclines in medicated feed for food-producing animals by HPLC–DAD - Elena Butovskaya; Alicia Maria Carrillo Heredero; Giulia Segato; Elena Faggionato; Marialuisa Borgia; Daniela Marchis; Simonetta Menotta; Simone Bertini (Food Additives & Contaminants: Part A, 2024)

Application of non-lethal bioSPME-LC-MS/MS for the detection of human pharmaceuticals in soft corals: A survey at the North Nilandhe atoll (Maldives) - Alessandro Becchi; Marco Mantovani; Marina Lasagni; Elena Collina; Simone Montano; Paolo Galli; Francesco Saliu (Chemosphere, 2024)

Investigating the Presence of Biomass Burning Events at Ny-Ålesund: Optical and Chemical Insights from Summer-Fall 2019 - Simone Pulimeno; Federica Bruschi; Matteo Feltracco; Mauro Mazzola; Stefania Gilardoni; Stefano Crocchianti; David Cappelletti; Andrea Gambaro; Elena Barbaro (Atmospheric Environment, 2024)

The Northernmost Records of Caranx crysos (Osteichthyes: Carangidae) in the NW Mediterranean Sea - Davide Di Blasi; Simone Bava; Elena Desiderà; Lorenzo Merotto; Federica Poli; Paolo Guidetti (Thalassas: An International Journal of Marine Sciences, 2024)

Signature of the anthropogenic impacts on the epipelagic microbiome of the North-Western Adriatic Sea (Mediterranean Sea) - Giulia Trapella; Daniel Scicchitano; Lucia Foresto; Andrea Nicoló Dell’Acqua; Elena Radaelli; Silvia Turroni; Simone Rampelli; Cinzia Corinaldesi; Giorgia Palladino; Marco Candela (Frontiers in Marine Science, 2024)
Introduction In our paper, we explored the impact of different anthropogenic stressors, namely, mussel farming, methane extraction platforms, and summer mass tourism, on the epipelagic microbiomes of the North-Western Adriatic Sea. Methods By 16S rRNA gene sequencing, we provided the epipelagic microbiome layout from selected sites corresponding to each of the considered impacts. As an unimpacted reference, we used already published 16S rRNA sequencing data. Results According to our findings, each one of the anthropogenic stressors resulted in a peculiar increase of specific epipelagic microbial components, including copiotrophic R-strategists and host-restricted bacteria, as well as some pathobiome components, the latter being detected exclusively in impacted sites. Particularly, potentially harmful pathogenic species such as Legionella impletisoli and Staphylococcus epidermidis have been detected in proximity to the mussel farms, and Escherichia coli and Campylobacter ureolyticus were present close to the methane extraction platform and at the summer mass tourism site, respectively. Particularly, C. ureolyticus is an emerging human gastrointestinal pathogen, capable of destroying intestinal microvilli. Discussion In addition to providing evidence supporting the existence of recognizable and impact-driven fingerprints on the epipelagic marine microbiome peculiar to the different anthropogenic stressors, our findings also raise concern about the ecological relevance of the observed changes, in terms of possible loss of ecosystem services and also for the potential release of pathogenic microorganisms in the environment.

A synchrotron X-ray scattering study of the crystallization behavior of mixtures of confectionary triacylglycerides: Effect of chemical composition and shear on polymorphism and kinetics - Elena Simone; Michael Rappolt; Holly Ewens; Tom Rutherford; Stephanie Marty Terrade; Francesca Giuffrida; Cynthia Marmet (Food Research International, 2024)

The ethical assessment of Assisted Reproductive Technologies (ART) in wildlife conservation - Barbara de Mori; Elena Mercugliano; Pierfrancesco Biasetti; Ilaria Pollastri; Maria Michela Spiriti; Daniela Florio; Francesco Andreucci; Frank Göritz; Susanne Holtze; Cesare Galli; Jan Stejskal; Silvia Colleoni; et al. (Biological Conservation, 2024)

Life cycle assessment of biostimulant production from algal biomass grown on piggery wastewater - Elena M. Rojo; Simone Rossi; Silvia Bolado; Paola Gallo Stampino; Elena Ficara; Giovanni Dotelli (Science of The Total Environment, 2024)

Removal of pharmaceutical compounds from the liquid phase of anaerobic sludge in a pilot-scale high-rate algae-bacteria pond - Marco Mantovani; Simone Rossi; Elena Ficara; Elena Collina; Francesca Marazzi; Marina Lasagni; Valeria Mezzanotte (Science of The Total Environment, 2024)

High-resolution climate variability across the Piacenzian/Gelasian boundary in the Monte San Nicola section (Sicily, Italy) - Elena Zanola; Sergio Bonomo; Alessandro Incarbona; Agata Di Stefano; Salvatore Distefano; Patrizia Ferretti; Eliana Fornaciari; Simone Galeotti; Patrizia Macrì; Isabella Raffi; Nadia Sabatino; Fabio Speranza; et al. (Quaternary Science Reviews, 2024)

LCA based circularity indices of systems at different scales: a holistic approach - Simone Bastianoni; Giulia Goffetti; Elena Neri; Nicoletta Patrizi; Anna Ruini; Fabio Sporchia; Federico M. Pulselli (Science of The Total Environment, 2023)

Different facets of the same niche: Integrating citizen science and scientific survey data to predict biological invasion risk under multiple global change drivers - Mirko Di Febbraro; Luciano Bosso; Mauro Fasola; Francesca Santicchia; Gaetano Aloise; Simone Lioy; Elena Tricarico; Luciano Ruggieri; Stefano Bovero; Emiliano Mori; Sandro Bertolino (Global Change Biology, 2023)
Citizen science initiatives have been increasingly used by researchers as a source of occurrence data to model the distribution of alien species. Since citizen science presence‐only data suffer from some fundamental issues, efforts have been made to combine these data with those provided by scientifically structured surveys. Surprisingly, only a few studies proposing data integration evaluated the contribution of this process to the effective sampling of species' environmental niches and, consequently, its effect on model predictions on new time intervals. We relied on niche overlap analyses, machine learning classification algorithms and ecological niche models to compare the ability of data from citizen science and scientific surveys, along with their integration, in capturing the realized niche of 13 invasive alien species in Italy. Moreover, we assessed differences in current and future invasion risk predicted by each data set under multiple global change scenarios. We showed that data from citizen science and scientific surveys captured similar species niches though highlighting exclusive portions associated with clearly identifiable environmental conditions. In terrestrial species, citizen science data granted the highest gain in environmental space to the pooled niches, determining an increased future biological invasion risk. A few aquatic species modelled at the regional scale reported a net loss in the pooled niches compared to their scientific survey niches, suggesting that citizen science data may also lead to contraction in pooled niches. For these species, models predicted a lower future biological invasion risk. These findings indicate that citizen science data may represent a valuable contribution to predicting future spread of invasive alien species, especially within national‐scale programmes. At the same time, citizen science data collected on species poorly known to citizen scientists, or in strictly local contexts, may strongly affect the niche quantification of these taxa and the prediction of their future biological invasion risk.

What motivates German consumers to reduce their meat consumption? Identifying relevant beliefs - Alice Elena Seffen; Simone Dohle (Appetite, 2023)

Philosophies of good living and values of nature: power and uncertainties in decision-making to achieve social-environmental justice in the Americas - Elena Lazos-Chavero; Agnieszka Pawlowska-Mainville; David González-Jiménez; Mariana Cantú-Fernández; Simone Athayde (Current Opinion in Environmental Sustainability, 2023)

Plant invasion risk inside and outside protected areas: Propagule pressure, abiotic and biotic factors definitively matter - Vanessa Lozano; Mirko Di Febbraro; Giuseppe Brundu; Maria Laura Carranza; Alessandro Alessandrini; Nicola Maria Giuseppe Ardenghi; Elena Barni; Gianni Bedini; Laura Celesti-Grapow; Kevin Cianfaglione; Annalena Cogoni; Gianniantonio Domina; et al. (Science of The Total Environment, 2023)

Correction to: Modulation of matrix metalloproteases by ciliary neurotrophic factor in human placental development - Giovanni Tossetta; Sonia Fantone; Elena Marinelli Busilacchi; Nicoletta Di Simone; Stefano R. Giannubilo; Giovanni Scambia; Antonio Giordano; Daniela Marzioni (Cell and Tissue Research, 2023)

Toxicology of 3-monochloropropane-1,2-diol and its esters: a narrative review - Elena Fattore; Alessia Lanno; Alberto Danieli; Simone Stefano; Alice Passoni; Alessandra Roncaglioni; Renzo Bagnati; Enrico Davoli (Archives of Toxicology, 2023)

Antifungal activity of a shortened analogue of the natural peptide LyeTx I isolated from the venom of the spider Lycosa erythrognatha - Bárbara Gatti Cardoso; William Gustavo de Lima; Simone Odília Antunes Fernandes; Maria Elena de Lima; Valbert Nascimento Cardoso (Natural Product Research, 2023)

Klebsiella pneumoniae carrying multiple alleles of antigen 43-encoding gene of Escherichia coli associated with biofilm formation - Martina Tambassi; Elena Passarini; Ilaria Menozzi; Melissa Berni; Chiara Bracchi; Alessandra Dodi; Luca Bolzoni; Erika Scaltriti; Marina Morganti; Giulia Ferrarini; Laura Sordi; Mario Sarti; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)
A clinical strain of Klebsiella pneumoniae typed as sequence type 307 carrying three different alleles of the flu gene encoding the Escherichia coli virulence factor antigen 43 associated with biofilm formation was detected and characterized. The flu alleles are located in the chromosome inside putative integrative conjugative elements. The strain displays the phenotypes associated with Ag43, i.e. bi-phasic colony morphology and enhanced biofilm production. Furthermore, the strain produces low amount of capsule known to affect Ag43 function. Analysis of 1431 worldwide deposited genomes revealed that 3.7% Klebsiella pneumoniae carry one or two flu alleles.

Pin-supported walls as seismic retrofit for existing RC frames: performance improvement through link removal - Elena Casprini; Andrea Belleri; Alessandra Marini; Chiara Passoni; Simone Labò (Bulletin of Earthquake Engineering, 2023)
Pin-supported (PS) walls represent a possible solution for the seismic retrofit of existing reinforced concrete (RC) buildings, enabling linearization of the frame deformation along its height and consequently inhibiting soft storey collapse mechanisms. The effectiveness of this rehabilitation technology is strongly related to the characteristics of the existing frames, especially to the vertical distribution of the frame storey lateral stiffness. Since a larger 1st storey lateral stiffness may lead to a detrimental structural response of the retrofitted system, an alternative solution obtained from removing the connecting link between the 1st floor of the existing building and the pin-supported wall is investigated in this paper. An analytical method is proposed to derive the distribution of the internal actions in a dual 2D RC frame-PS wall system without the link at the 1st floor level, considering both a linear and nonlinear behaviour of the frame. It emerges that some parameters describing the structure type can provide straightforward information on the suitability of this solution in the seismic retrofit of existing RC buildings. As a result, a simplified procedure has been derived to preliminarily define the retrofit system configuration and evaluate the maximum demand in the PS wall. Such a procedure is finally applied with reference to a frame representing a RC building and finite element model analyses are carried out for validation purposes.

Clinical impact of rare variants associated with inherited channelopathies: a 5-year update - Georgia Sarquella-Brugada; Anna Fernandez-Falgueras; Sergi Cesar; Elena Arbelo; Mónica Coll; Alexandra Perez-Serra; Marta Puigmulé; Anna Iglesias; Mireia Alcalde; Marta Vallverdú-Prats; Victoria Fiol; Carles Ferrer-Costa; et al. (Human Genetics, 2022)
A proper interpretation of the pathogenicity of rare variants is crucial before clinical translation. Ongoing addition of new data may modify previous variant classifications; however, how often a reanalysis is necessary remains undefined. We aimed to extensively reanalyze rare variants associated with inherited channelopathies originally classified 5 years ago and its clinical impact. In 2016, rare variants identified through genetic analysis were classified following the American College of Medical Genetics and Genomics’ recommendations. Five years later, we have reclassified the same variants following the same recommendations but including new available data. Potential clinical implications were discussed. Our cohort included 49 cases of inherited channelopathies diagnosed in 2016. Update show that 18.36% of the variants changed classification mainly due to improved global frequency data. Reclassifications mostly occurred in minority genes associated with channelopathies. Similar percentage of variants remain as deleterious nowadays, located in main known genes ( SCN5A, KCNH2 and KCNQ1 ). In 2016, 69.38% of variants were classified as unknown significance, but now, 53.06% of variants are classified as such, remaining the most common group. No management was modified after translation of genetic data into clinics. After 5 years, nearly 20% of rare variants associated with inherited channelopathies were reclassified. This supports performing periodic reanalyses of no more than 5 years since last classification. Use of newly available data is necessary, especially concerning global frequencies and family segregation. Personalized clinical translation of rare variants can be crucial to management if a significant change in classification is identified.

Modulation of matrix metalloproteases by ciliary neurotrophic factor in human placental development - Giovanni Tossetta; Sonia Fantone; Elena Marinelli Busilacchi; Nicoletta Di Simone; Stefano R. Giannubilo; Giovanni Scambia; Antonio Giordano; Daniela Marzioni (Cell and Tissue Research, 2022)
Ciliary neurotrophic factor (CNTF) is a pleiotropic cytokine that signals through a receptor complex containing a specific subunit, CNTF receptor α (CNTFRα). The two molecules are constitutively expressed in key structures for human placental growth and differentiation. The possible role of CNTF in enhancing cell proliferation and/or invasion during placental development and remodelling was investigated using HTR-8/SVneo and BeWo cells, taken respectively as cytotrophoblast and syncytiotrophoblast models. In both cell lines, treatment with human recombinant (hr) CNTF activated JAK2/STAT3 signalling and inhibited the ERK pathway. Interestingly, in HTR-8/SVneo cells, 50 ng hrCNTF induced significant downregulation of matrix metalloprotease (MMP)-1 and significant upregulation of MMP-9. Moreover, pharmacological inhibition of JAK2/STAT3 signalling by AG490 and curcumin resulted in MMP-9 downregulation; it activated the ERK signalling pathway and upregulated MMP-1 expression. Collectively, these data suggest a role for CNTF signalling in extravillous cytotrophoblast invasion through the modulation of specific MMPs.

Treatment duration for central line-associated infection caused by Enterococcus spp.: a retrospective evaluation of a multicenter cohort - Elena Rosselli Del Turco; Zeno Pasquini; Kristian Scolz; Alberto Amedeo; Giacomo Beci; Maddalena Giglia; Linda Bussini; Sulamita Carvalho-Brugger; Laura Gutiérrez; Sara Tedeschi; Mercè Garcia; Simone Ambretti; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2022)

Pin-supported walls as seismic retrofit for existing RC frames: feasibility and preliminary design - Elena Casprini; Andrea Belleri; Alessandra Marini; Simone Labò; Chiara Passoni (Bulletin of Earthquake Engineering, 2022)
The seismic retrofit of the existing building heritage represents an urgent issue to be faced and innovative solutions which allow to overcome renovation barriers are needed. In this scenario, pin-supported (PS) walls represent an eligible solution, enabling linearization of the deformation of the frame along its height and inhibiting soft storey collapse mechanisms. The PS wall can be connected to the existing building from outside, thereby avoiding disruption to occupants or their relocation, which are acknowledged as the main barriers to the renovation nowadays. Suitability of PS wall solutions in the seismic retrofit of the existing building stock has been investigated herein, particularly in the case of existing reinforced concrete (RC) buildings, preliminarily focusing on 2D RC frames. The paper shows the weaknesses and strengths of the PS wall solution in relation to the specific features of the considered buildings. An analytical closed-form formulation is proposed and applied as a preliminary tool to evaluate the load distribution in the existing frame and in the PS wall after the retrofit considering the first mode of vibration of the retrofitted system. The results show that, in some conditions, the application of PS walls may be detrimental to the structural response. Along with the evaluation of the effectiveness of the retrofit solution, the proposed formulation allows a preliminary design of the retrofit system. Finally, a series of finite element model analyses have been carried out for validation purposes showing a good agreement between the proposed analytical formulation and the numerical results.

The Important Marine Mammal Area Network: A Tool for Systematic Spatial Planning in Response to the Marine Mammal Habitat Conservation Crisis - Michael J. Tetley; Gill T. Braulik; Caterina Lanfredi; Gianna Minton; Simone Panigada; Elena Politi; Margherita Zanardelli; Giuseppe Notarbartolo di Sciara; Erich Hoyt (Frontiers in Marine Science, 2022)
The Important Marine Mammal Areas (IMMAs) initiative was launched by the Marine Mammal Protected Areas Task Force of the International Union for the Conservation of Nature in 2016, as a response to a conservation crisis in the protection of marine mammals and wider global ocean biodiversity. IMMAs identify discrete portions of habitat that are important for one or more marine mammal species, and that have the potential to be delineated and managed for conservation. They are identified by scientific experts during regional workshops, on the basis of satisfying one or more of eight criteria that capture critical aspects of marine mammal biology, ecology and population structure. Candidate IMMAs undergo independent scientific review prior to being accepted, and then are publicly available via a searchable and downloadable database and a dedicated online e-Atlas. Between 2016 and 2021, eight expert workshops - engaging more than 300 experts - have resulted in the identification of 173 IMMAs located in 90 countries or territories, across a third of the globe. IMMAs identified to date provide important habitats for 58 of the 131 recognized marine mammal species. Around two-thirds of all IMMAs (65%) were identified on the basis of important habitat for a marine mammal species that is threatened on the IUCN Red List. Approximately 61% of IMMA surface areas occur within Exclusive Economic Zone waters, while 39% fall within areas beyond national jurisdiction. The Task Force undertook implementation planning exercises for IMMAs in Palau (Micronesia), the Andaman Islands (India) and the Bazaruto Archipelago and Inhambane Bay (Mozambique), engaging with a range of stakeholders including government and management bodies. IMMAs are increasingly being utilized in environmental impact assessments, marine planning exercises and in international, national and supra-regional conservation, policy and management initiatives, including the Convention on Migratory Species and Convention on Biological Diversity, as well as the design and management of Marine Protected Areas (MPAs) and the extension of MPA networks. The Task Force is working toward completing a global network of IMMAs that will contribute the scientific information needed to fulfill the current collective goal of protecting 30% of the ocean by 2030.

Defend as You Can, React Quickly: The Effects of the COVID-19 Shock on a Large Fishery of the Mediterranean Sea - Tommaso Russo; Elena Catucci; Simone Franceschini; Lucio Labanchi; Simone Libralato; Evelina Carmen Sabatella; Rosaria Felicita Sabatella; Antonio Parisi; Fabio Fiorentino (Frontiers in Marine Science, 2022)
This paper presents an analysis of the effect of SARS-CoV-2 coronavirus pandemic and related restrictive measures on the activity of the Italian fleet of trawlers, which represents one of the most important fisheries in the Mediterranean Sea. We integrated multiple sources of information including: (1) Fleet activity data from Vessel Monitoring System, the most important satellite-based tracking device; (2) vessel-specific landing data disaggregated by species; (3) market and economic drivers affecting the effort variation during the lockdown and in the related fishing strategies; (4) monthly landings of demersal species in the main Italian harbors. These data sources are combined to: (1) Assess the absolute and relative changes of trawling effort in the geographical sub-areas surrounding the Italian coasts; (2) integrate and compare these changes with the market and economic drivers in order to explain the observed changes in fishing effort and strategy; (3) analyze the changes of the fishing effort on the Landing-per-unit-effort (LPUE) in order to further understand the strategy adopted by fishers during this crisis and to infer the potential consequence for the different stocks. The results provide an overview of the effects of the “COVID-19 shock,” in terms of fishing activity and socio-economic drivers, demonstrating that the consequences of the pandemic have been very varied. Although the COVID-19 shock has caused a marked overall reduction in activity in the first semester of 2020, in some cases the strategies adopted by fishermen and the commercial network linked to their activity have significantly reduced the impact of the emergency and taken back catch and effort to levels similar to those of previous years. These results could provide insights for management measures based on temporal stops of fishing activities. In particular, if no limits to the fishing effort after the restart of fishing activities are adopted, the benefits of fishing pressure reduction on fishery resources could be nullified. On the other hands, when fishing activities restart, and in the absence of catch control, effort tends to increase on coastal bottoms characterized by greater abundance of resources and longer effective fishing time.

Richer, greener, and more thermophilous? – a first overview of global warming induced changes in the Italian alpine plant communities within the new GLORIA ITALIA NETWORK - Francesco Porro; Simone Orsenigo; Thomas Abeli; Andrea Mondoni; Anna Corli; Fiona J. White; Silvano Lodetti; Marcello Tomaselli; Alessandro Petraglia; Michele Carbognani; Matteo Gualmini; T’ai G. W. Forte; et al. (Plant Biosystems, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Plastic and Us: looking at the marine litter problem from inside the rubbish. An unusual temporary exhibition at the Natural History Museum of the University of Pisa - SILVIA MERLINO; MARINA LOCRITANI; SIMONE FARINA; CHIARA SORBINI; SILVIA BATTAGLINI; MARCO DELLACASA; PATRIZIA SCAGLIA; DAMIANO MARCHI; ELENA BONACCORSI (Mediterranean Marine Science, 2021)
In this paper, we will describe a temporary exhibition held at the Museo di Storia Naturale dell’Università di Pisa (Natural History Museum of the University of Pisa, hereafter MSN), Italy, in year 2020-2021, and the educational and awareness raising results that the proposed approach has produced. The aim of this exhibition was to guide the visitor along a path of awareness on the very topical issue of “plastic in our environment”. It focused not only on the environmental impact produced by the dispersal of anthropogenic plastic waste, especially in the sea, but also on the awareness of what actions need to be taken, both on a governmental and personal level, by each of us, to limit it in the future. The exhibition started from the data and images proposed by the media, which shocked us with the seriousness of the plastic emergency and triggered worldwide attention. Then the emphasis of the exhibition shifted to scientific data, rigorously presented by researchers who study the issue directly in the field, in the Mediterranean Sea and along its coasts. Finally, the last exhibits addressed the issue of plastic disposal, inviting visitors to check their real knowledge about the concepts of degradable, compostable, or recyclable plastic, and to reflect on what could be the most effective means to limit plastic problems in the future. The plastic problem is exquisitely anthropogenic, and the exhibit was designed to make visitors feel involved. The mismanagement of the lifecycle of this material (from manufacturing processes to products’ end life) can be addressed on a global scale by drastically reducing the use and production of single-use plastic items, promoting proper waste management, and improving the effectiveness of recycling. The exhibition message was that laws are essential, as well as calling plastic producers to their responsibility, but something can also be done locally by us as individuals, through proper disposal and by producing less single-use plastic waste. Visitors' attitudes and knowledge on this topic were investigated through online questionnaires prepared by experts in the field, and the data collected are presented and discussed in this paper.

IDPlanT: the Italian database of plant translocation - Thomas Abeli; Martina D’Agostino; Simone Orsenigo; Fabrizio Bartolucci; Rita Accogli; Giulia Albani Rocchetti; Claudia Alessandrelli; Arianna Amadori; Filippo Amato; Claudia Angiolini; Silvia Assini; Gianluigi Bacchetta; et al. (Plant Biosystems, 2021)

Conservation status of the Italian flora under the 92/43/EEC ‘Habitats’ Directive - Giuseppe Fenu; Consolata Siniscalco; Gianluigi Bacchetta; Donatella Cogoni; Maria Silvia Pinna; Marco Sarigu; Thomas Abeli; Elena Barni; Fabrizio Bartolucci; Daniela Bouvet; Annalena Cogoni; Fabio Conti; et al. (Plant Biosystems, 2021)

Women’s empowerment and gender equality in agricultural value chains: evidence from four countries in Asia and Africa - Agnes Quisumbing; Jessica Heckert; Simone Faas; Gayathri Ramani; Kalyani Raghunathan; Hazel Malapit; Hazel Malapit; Jessica Heckert; Sarah Eissler; Simone Faas; Elena Martinez; Emily Myers; et al. (Food Security, 2021)
Women play important roles at different nodes of both agricultural and off-farm value chains, but in many countries their contributions are either underestimated or limited by prevailing societal norms or gender-specific barriers. We use primary data collected in Asia (Bangladesh, Philippines) and Africa (Benin, Malawi) to examine the relationships between women’s empowerment, gender equality, and participation in a variety of local agricultural value chains that comprise the food system. We find that the value chain and the specific node of engagement matter, as do other individual and household characteristics, but in different ways depending on country context. Entrepreneurship—often engaged in by wealthier households with greater ability to take risks—is not necessarily empowering for women; nor is household wealth, as proxied by their asset ownership. Increased involvement in the market is not necessarily correlated with greater gender equality. Education is positively correlated with higher empowerment of both men and women, but the strength of this association varies. Training and extension services are generally positively associated with empowerment but could also exacerbate the inequality in empowerment between men and women in the same household. All in all, culture and context determine whether participation in value chains—and which node of the value chain—is empowering. In designing food systems interventions, care should be taken to consider the social and cultural contexts in which these food systems operate, so that interventions do not exacerbate existing gender inequalities.

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Impact of Plastic Debris on the Gut Microbiota of Caretta caretta From Northwestern Adriatic Sea - Elena Biagi; Margherita Musella; Giorgia Palladino; Valeria Angelini; Sauro Pari; Chiara Roncari; Daniel Scicchitano; Simone Rampelli; Silvia Franzellitti; Marco Candela (Frontiers in Marine Science, 2021)
Plastic pollution is nowadays a relevant threat for the ecological balance in marine ecosystems. Small plastic debris (PD) can enter food webs through various marine organisms, with possible consequences on their physiology and health. The loggerhead sea turtle ( Caretta caretta ), widespread across the whole Mediterranean Sea, is a “flagship species,” useful as indicator of the general pollution level of marine ecosystems. Ingested PD accumulate in the final section of turtles’ digestive tract before excretion. During their transit and accumulation, PD also interact with the residing microbial community, with possible feedback consequences on the host’s health. To explore the possible relationship between fecal microbial composition and PD ingestion, we collected fecal samples from 45 turtles rescued between 2017 and 2019 in the Northwestern Adriatic Sea (Italy), assessing occurrence and content of PD in the samples and in parallel the microbiome structure by 16S rRNA gene sequencing. According to our findings, almost all samples contained PD, mirroring the high level of plastic pollution in the area. We identified phylotypes associated to a high amount of PD, namely Cetobacterium somerae and other taxa, possibly responding to contamination by plastic-associated chemicals. Furthermore, putative marine pathogens were found associated to higher plastic contamination, supporting the hypothesis that PD can act as a carrier for environmental pathogenic bacteria into marine organisms. Besides confirming the role of the sea turtle as relevant flagship species for plastic pollution of the marine environment, our study paves the way to the exploration of the impact that PD ingestion can have on the microbial counterpart of large marine organisms, with potential feedback consequences on the animal and ecosystem health.

Seasonal Changes in Microbial Communities Associated With the Jewel Anemone Corynactis viridis - Giorgia Palladino; Elena Biagi; Simone Rampelli; Margherita Musella; Federica D’Amico; Silvia Turroni; Patrizia Brigidi; Gian Marco Luna; Marco Candela (Frontiers in Marine Science, 2021)
Increasing evidence indicates that host-associated microbial communities play a key role in the biology of marine eukaryotic organisms. Amongst them, Corallimorpharia are extensively found on reefs, carpeting vast reef areas, where they can exert important roles as habitat forming holobionts, being at the base of complex trophic webs. Here we explore the bacterial community structure, and its changes across different seasons, associated with the jewel anemone Corynactis viridis , an anthozoan Cnidaria that is widely distributed in the northeastern Atlantic Ocean and the Mediterranean Sea. Samples were collected in the North Adriatic Sea in three seasons and the community composition was studied using 16S rDNA sequencing. We show that C. viridis- associated microbial communities are unique and significantly different from those in the surrounding seawater. Interestingly, we observe remarkable changes in the C. viridis microbiome according to seasonality. In particular, the C. viridis microbiome is capable of rearranging its overall ecological structure with the winter-summer transition, moving from an oligotrophic anaerobic community to a heterotrophic ecosystem, with the propensity to ferment proteins and complex polysaccharides. Our findings demonstrate that C. viridis has a unique associated microbiota and suggest that this is capable of adapting to seasonal changes in the host physiology, by establishing a microbiome-host interaction process whose relevance to C. viridis has yet to be determined.

Reproducing macaque lateral grasping and oculomotor networks using resting state functional connectivity and diffusion tractography - Henrietta Howells; Luciano Simone; Elena Borra; Luca Fornia; Gabriella Cerri; Giuseppe Luppino (Brain Structure and Function, 2020)
Cortico-cortical networks involved in motor control have been well defined in the macaque using a range of invasive techniques. The advent of neuroimaging has enabled non-invasive study of these large-scale functionally specialized networks in the human brain; however, assessing its accuracy in reproducing genuine anatomy is more challenging. We set out to assess the similarities and differences between connections of macaque motor control networks defined using axonal tracing and those reproduced using structural and functional connectivity techniques. We processed a cohort of macaques scanned in vivo that were made available by the open access PRIME-DE resource, to evaluate connectivity using diffusion imaging tractography and resting state functional connectivity (rs-FC). Sectors of the lateral grasping and exploratory oculomotor networks were defined anatomically on structural images, and connections were reproduced using different structural and functional approaches (probabilistic and deterministic whole-brain and seed-based tractography; group template and native space functional connectivity analysis). The results showed that parieto-frontal connections were best reproduced using both structural and functional connectivity techniques. Tractography showed lower sensitivity but better specificity in reproducing connections identified by tracer data. Functional connectivity analysis performed in native space had higher sensitivity but lower specificity and was better at identifying connections between intrasulcal ROIs than group-level analysis. Connections of AIP were most consistently reproduced, although those connected with prefrontal sectors were not identified. We finally compared diffusion MR modelling with histology based on an injection in AIP and speculate on anatomical bases for the observed false negatives. Our results highlight the utility of precise ex vivo techniques to support the accuracy of neuroimaging in reproducing connections, which is relevant also for human studies.

Increased CD4/CD8 ratio as a risk factor for critical illness in coronavirus disease 2019 (COVID-19): a retrospective multicentre study - Carlo Pallotto; Lorenzo Roberto Suardi; Sara Esperti; Roberto Tarquini; Elisa Grifoni; Simone Meini; Alice Valoriani; Stefania Di Martino; Francesco Cei; Eleonora Sisti; Fiorella Piani; Annarita Botta; et al. (Infectious Diseases, 2020)

Alpine tundra species phenology is mostly driven by climate-related variables rather than by photoperiod - Elena Quaglia; Simone Ravetto Enri; Elisa Perotti; Massimiliano Probo; Giampiero Lombardi; Michele Lonati (Journal of Mountain Science, 2020)
The study of plant phenology has frequently been used to link phenological events to various factors, such as temperature or photoperiod. In the high-alpine environment, proper timing of the phenological cycle has always been crucial to overcome harsh conditions and potential extreme events (i.e. spring frosts) but little is known about the response dynamics of the vegetation, which could shape the alpine landscape in a future of changing climate. Alpine tundra vegetation is composed by an array of species belonging to different phytosociological optima and with various survival strategies, and snowbed communities are a relevant expression of such an extreme-climate adapted flora. We set eight permanent plots with each one in a snowbed located on the Cimalegna plateau in Northwestern Italy and then we selected 10 most recurring species among our plots, all typical of the alpine tundra environment and classified in 3 different pools: snowbed specialists, grassland species and rocky debris species. For 3 years we registered the phenophases of each species during the whole growing season using an adaptation of the BBCH scale. We later focused on the three most biologically relevant phenophases, i.e., flower buds visible, full flowering, and beginning of seed dispersion. Three important season-related variables were chosen to investigate their relationship with the phenological cycle of the studied species: (i) the Day Of Year (DOY), the progressive number of days starting from the 1 st of January, used as a proxy of photoperiod, (ii) Days From Snow Melt (DFSM), selected to include the relevance of the snow dynamics, and (iii) Growing Degree Days (GDD), computed as a thermal sum. Our analysis highlighted that phenological development correlated better with DFSM and GDD than with DOY. Indeed, models showed that DOY was always a worse predictor since it failed to overcome interannual variations, while DFSM and marginally GDD were better suited to predict the phenological development of most of the species, despite differences in temperature and snowmelt date among the three years. Even if the response pattern to the three variables was mainly consistent for all the species, the timing of their phenological response was different. Indeed, species such as Salix herbacea and Ranunculus glacialis were always earlier in the achievement of the phenophases, while Agrostis rupestris and Euphrasia minima developed later and the remaining species showed an intermediate behavior. However, we did not detect significant differences among the three functional pools of species.

Rate of polymyxin resistance among Acinetobacter baumannii recovered from hospitalized patients: a systematic review and meta-analysis - William Gustavo Lima; Júlio César Moreira Brito; Bárbara Gatti Cardoso; Valbert Nascimento Cardoso; Magna Cristina de Paiva; Maria Elena de Lima; Simone Odília Antunes Fernandes (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Temporal Changes in Microbial Communities Beneath Fish Farm Sediments Are Related to Organic Enrichment and Fish Biomass Over a Production Cycle - Grazia Marina Quero; Francesca Ape; Elena Manini; Simone Mirto; Gian Marco Luna (Frontiers in Marine Science, 2020)

Neutralization of extracellular NAMPT (nicotinamide phosphoribosyltransferase) ameliorates experimental murine colitis - Giorgia Colombo; Nausicaa Clemente; Andrea Zito; Cristiano Bracci; Federico Simone Colombo; Sabina Sangaletti; Elena Jachetti; Davide Giuseppe Ribaldone; Gian Paolo Caviglia; Luca Pastorelli; Marco De Andrea; Samuele Naviglio; et al. (Journal of Molecular Medicine, 2020)

Plant–environment interactions through a functional traits perspective: a review of Italian studies - Stefano Chelli; Michela Marignani; Elena Barni; Alessandro Petraglia; Giacomo Puglielli; Camilla Wellstein; Alicia T. R. Acosta; Rossano Bolpagni; Luca Bragazza; Giandiego Campetella; Alessandro Chiarucci; Luisa Conti; et al. (Plant Biosystems, 2019)

Challenges for Sustained Observing and Forecasting Systems in the Mediterranean Sea - Joaquín Tintoré; Nadia Pinardi; Enrique Álvarez-Fanjul; Eva Aguiar; Diego Álvarez-Berastegui; Marco Bajo; Rosa Balbin; Roberto Bozzano; Bruno Buongiorno Nardelli; Vanessa Cardin; Benjamin Casas; Miguel Charcos-Llorens; et al. (Frontiers in Marine Science, 2019)

Intensive tobacco cultivations, a possible public health risk? - Giuseppe Michele Masanotti; Elia Abbafati; Elena Petrella; Simone Vinciguerra; Fabrizio Stracci (Environmental Science and Pollution Research, 2019)

Toward Improving Safety in Neurosurgery with an Active Handheld Instrument - Sara Moccia; Simone Foti; Arpita Routray; Francesca Prudente; Alessandro Perin; Raymond F. Sekula; Leonardo S. Mattos; Jeffrey R. Balzer; Wendy Fellows-Mayle; Elena De Momi; Cameron N. Riviere (Annals of Biomedical Engineering, 2018)

Modeling ozone uptake by urban and peri-urban forest: a case study in the Metropolitan City of Rome - Lina Fusaro; Simone Mereu; Elisabetta Salvatori; Elena Agliari; Silvano Fares; Fausto Manes (Environmental Science and Pollution Research, 2018)

Cortical and subcortical connections of parietal and premotor nodes of the monkey hand mirror neuron network - Stefania Bruni; Marzio Gerbella; Luca Bonini; Elena Borra; Gino Coudé; Pier Francesco Ferrari; Leonardo Fogassi; Monica Maranesi; Francesca Rodà; Luciano Simone; Francesca Ugolotti Serventi; Stefano Rozzi (Brain Structure and Function, 2017)

Characterization of the human DNA gut virome across populations with different subsistence strategies and geographical origin - Simone Rampelli; Silvia Turroni; Stephanie L. Schnorr; Matteo Soverini; Sara Quercia; Monica Barone; Andrea Castagnetti; Elena Biagi; Giorgio Gallinella; Patrizia Brigidi; Marco Candela (Environmental Microbiology, 2017)
Summary It is a matter of fact that the human gut microbiome also includes a non‐bacterial fraction represented by eukaryotic cells and viruses. To further explore the gut microbiome variation in human populations, here we characterized the human DNA viral community from publicly available gut metagenome data sets from human populations with different geographical origin and lifestyle. In particular, such data sets encompass microbiome information from two western urban societies (USA and Italy), as well as two traditional hunter‐gatherer communities (the Hadza from Tanzania and Matses from Peru) and one pre‐agricultural tribe (Tunapuco from Peru). Our results allowed for the first taxonomic reconstruction of the complex viral metacommunities within the human gut. The core virome structure included herpesviruses, papillomaviruses, polyomaviruses, adenoviruses and anelloviruses. Using Random Forests and a co‐occurrence analysis approach, we identified the viruses that distinguished populations according to their geographical origin and/or lifestyle. This paves the way for new research aimed at investigating the biological role of the gut virome in human physiology, and the importance of our viral counterpart in the microbiome‐host co‐evolutionary process.

Risk factors for recurrent carbapenem resistant Klebsiella pneumoniae bloodstream infection: a prospective cohort study - Maddalena Giannella; Elena Graziano; Lorenzo Marconi; Nicolo Girometti; Michele Bartoletti; Sara Tedeschi; Fabio Tumietto; Francesco Cristini; Simone Ambretti; Andrea Berlingeri; Russell E. Lewis; Pierluigi Viale (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Is it time to revise linezolid dose in elderly patients? - Marco Tinelli; Cristina Gervasoni; Manuela Piazza; Roberta Terzi; Valeria Cozzi; Elena Maffezzini; Chiara Cerri; Simone Castoldi; Sara Baldelli; Dario Cattaneo (European Journal of Clinical Pharmacology, 2017)

Long-term life cycle and massive blooms of the intertidal hydroid Paracoryne huvei in the North-western Mediterranean Sea - Federico Betti; Giorgio Bavestrello; Carlo Nike Bianchi; Carla Morri; Elena Righetti; Simone Bava; Marzia Bo (Marine Biology Research, 2017)

High adaptive variability and virus-driven selection on major histocompatibility complex (MHC) genes in invasive wild rabbits in Australia - Nina Schwensow; Camila J. Mazzoni; Elena Marmesat; Joerns Fickel; David Peacock; John Kovaliski; Ron Sinclair; Phillip Cassey; Brian Cooke; Simone Sommer (Biological Invasions, 2017)

The contribution of Potamogeton crispus to the phosphorus budget of an urban shallow lake: Lake Monger, Western Australia - Barbara Leoni; Clelia Luisa Marti; Elena Forasacco; Matteo Mattavelli; Valentina Soler; Pietro Fumagalli; Jörg Imberger; Simone Rezzonico; Letizia Garibaldi (Limnology, 2016)

Plant use and local vegetation patterns during the second half of the Late Pleistocene in southwestern Germany - Simone Riehl; Elena Marinova; Katleen Deckers; Maria Malina; Nicholas J. Conard (Archaeological and Anthropological Sciences, 2015)

Mapping global cropland and field size - Steffen Fritz; Linda See; Ian McCallum; Liangzhi You; Andriy Bun; Elena Moltchanova; Martina Duerauer; Fransizka Albrecht; Christian Schill; Christoph Perger; Petr Havlik; Aline Mosnier; et al. (Global Change Biology, 2015)
A new 1 km global IIASA ‐ IFPRI cropland percentage map for the baseline year 2005 has been developed which integrates a number of individual cropland maps at global to regional to national scales. The individual map products include existing global land cover maps such as GlobCover 2005 and MODIS v.5, regional maps such as AFRICOVER and national maps from mapping agencies and other organizations. The different products are ranked at the national level using crowdsourced data from Geo‐Wiki to create a map that reflects the likelihood of cropland. Calibration with national and subnational crop statistics was then undertaken to distribute the cropland within each country and subnational unit. The new IIASA ‐ IFPRI cropland product has been validated using very high‐resolution satellite imagery via Geo‐Wiki and has an overall accuracy of 82.4%. It has also been compared with the EarthStat cropland product and shows a lower root mean square error on an independent data set collected from Geo‐Wiki. The first ever global field size map was produced at the same resolution as the IIASA ‐ IFPRI cropland map based on interpolation of field size data collected via a Geo‐Wiki crowdsourcing campaign. A validation exercise of the global field size map revealed satisfactory agreement with control data, particularly given the relatively modest size of the field size data set used to create the map. Both are critical inputs to global agricultural monitoring in the frame of GEOGLAM and will serve the global land modelling and integrated assessment community, in particular for improving land use models that require baseline cropland information. These products are freely available for downloading from the http://cropland.geo-wiki.org website.

Using a citizen science program to monitor coral reef biodiversity through space and time - Simone Branchini; Francesco Pensa; Patrizia Neri; Bianca Maria Tonucci; Lisa Mattielli; Anna Collavo; Maria Elena Sillingardi; Corrado Piccinetti; Francesco Zaccanti; Stefano Goffredo (Biodiversity and Conservation, 2015)

Investigating the immunodominance of carbohydrate antigens in a bivalent unimolecular glycoconjugate vaccine against serogroup A and C meningococcal disease - Roberto Adamo; Alberto Nilo; Carole Harfouche; Barbara Brogioni; Simone Pecetta; Giulia Brogioni; Evita Balducci; Vittoria Pinto; Sara Filippini; Elena Mori; Marta Tontini; Maria Rosaria Romano; et al. (Glycoconjugate Journal, 2014)

Patient-specific generation of the Purkinje network driven by clinical measurements of a normal propagation - Christian Vergara; Simone Palamara; Domenico Catanzariti; Fabio Nobile; Elena Faggiano; Cesarino Pangrazzi; Maurizio Centonze; Massimiliano Maines; Alfio Quarteroni; Giuseppe Vergara (Medical & Biological Engineering & Computing, 2014)

ATP synthesis and storage - Massimo Bonora; Simone Patergnani; Alessandro Rimessi; Elena De Marchi; Jan M. Suski; Angela Bononi; Carlotta Giorgi; Saverio Marchi; Sonia Missiroli; Federica Poletti; Mariusz R. Wieckowski; Paolo Pinton (Purinergic Signalling, 2012)

Establishing climatic constraints shaping the distribution of alien plant species along the elevation gradient in the Alps - Elena Barni; Giovanni Bacaro; Simone Falzoi; Federico Spanna; Consolata Siniscalco (Plant Ecology, 2012)

Diet and the risk of head and neck cancer: a pooled analysis in the INHANCE consortium - Shu-Chun Chuang; Mazda Jenab; Julia E. Heck; Cristina Bosetti; Renato Talamini; Keitaro Matsuo; Xavier Castellsague; Silvia Franceschi; Rolando Herrero; Deborah M. Winn; Carlo La Vecchia; Hal Morgenstern; et al. (Cancer Causes & Control, 2012)

Study of the Adhesion of Bifidobacterium bifidum MIMBb75 to Human Intestinal Cell Lines - Simone Guglielmetti; Isabella Tamagnini; Mario Minuzzo; Stefania Arioli; Carlo Parini; Elena Comelli; Diego Mora (Current Microbiology, 2009)

Carthamus species in the ancient Near East and south-eastern Europe: archaeobotanical evidence for their distribution and use as a source of oil - Elena Marinova; Simone Riehl (Vegetation History and Archaeobotany, 2009)

Mid-Holocene vegetation change in the Troad (W Anatolia): man-made or natural? - Simone Riehl; Elena Marinova (Vegetation History and Archaeobotany, 2008)

Animal xenodiversity in Italian inland waters: distribution, modes of arrival, and pathways - Francesca Gherardi; Sandro Bertolino; Marco Bodon; Sandra Casellato; Simone Cianfanelli; Marco Ferraguti; Elisabetta Lori; Graziella Mura; Annamaria Nocita; Nicoletta Riccardi; Giampaolo Rossetti; Emilia Rota; et al. (Biological Invasions, 2008)

Borrelia lusitaniae OspA Gene Heterogeneity in Mediterranean Basin Area - Elena Grego; Luigi Bertolotti; Simone Peletto; Giuseppina Amore; Laura Tomassone; Alessandro Mannelli (Journal of Molecular Evolution, 2007)